Working Group Recommendations for the Practice of Teleneuropsychology in Latin America. (20th October 2021) - Crivelli, Lucía; Quiroz, Yakeel T; Calandri, Ismael L; Martin, María E; Velilla, Lina M; Cusicanqui, María I; Yglesias, Fernando Coto; Llibre-Rodríguez, Juan J; Armele, Monserrat; Román, Fabián; Barceló, Ernesto; Dechent, Claudia; et al.
Abstract: Objective: Teleneuropsychology (teleNP) could potentially expand access to services for patients who are confined, have limited personal access to healthcare, or live in remote areas. The emergence of the COVID-19 pandemic has significantly increased the use of teleNP for cognitive assessments. The main objective of these recommendations is to identify which procedures can be potentially best adapted to the practice of teleNP in Latin America, and thereby facilitate professional decision-making in the region. Method: Steps taken to develop these recommendations included (1) formation of an international working group with representatives from 12 Latin American countries; (2) assessment of rationale, scope, and objectives; (3) formulation of clinical questions; (4) evidence search and selection; (5) evaluation of existing evidence and summary; and (6) formulation of recommendations. Levels of evidence were graded following the Oxford Centre for Evidence-Based Medicine system. Databases examined included PubMed, WHO-IRIS, WHO and PAHO-IRIS, Índice Bibliográfico Español en Ciencias de la Salud (IBCS), and LILACS. Results: Working group members reviewed 18, 400 titles and 422 abstracts and identified 19 articles meeting the criteria for level of evidence, categorization, and elaboration of recommendations. The vast majority of the literature included teleNP tests in the English language. The working group proposed a series of recommendations that can be potentially best adapted to the practice of teleNP in Latin America. Conclusions: There is currently sufficient evidence to support the use of videoconferencing technology for remote neuropsychological assessments. These recommendations will likely contribute to the advancement of teleNP research and practice in the region.